A Comparative Study of Atherosclerosis and Myocardial Infarction Knowledge among Pharmacy Students in Dharashiv, India - Kashyap, Saurabh; Jha, Deepak; Hangargekar, Pallavi; Ram, Priyanshu; Joshi, Amol; Jain, Ashish (Indian Journal of Pharmacy Practice)
Background: The Health Related Quality of Life (HRQL) is concerned with understanding how health influences an individual capacity to lead satisfying life. Patient-centric outcome surveys are frequently employed to evaluate and track HRQL. Medical outcome study of short form (sf-36) Health Survey is commonly utilized general tool to assess the HRQL, comprising thirty-six questions across eight dimensions. To gauge health within a community, a dependable and validated tool is essential. Objectives: To assess the quality of life related to health in individuals and to predict their overall health status, aiding in the diagnosis of their overall well-being. Facilitating the diagnosis of the patient’s general well-being. Additionally, this evaluation proves valuable for future research endeavors. Materials and Methods: Conducting a study based on the population, the SF-36 Hindi questionnaire was given for a cohort comprising 543 healthy individuals with an average aged 18 years or older in Udaipur and its surrounding villages. Data collection was conducted by trained interviewers and all participants have been interviewed at their respective locations. The translated SF-36 Hindi was administered and was filled by the individuals itself. Statistical analyses were carried out for establishing the validity and reliability of the scale-level items. To examine the high order factor structures and the principal component analysis with varimax rotation was employed. Results: Total 543 individuals surveyed, 65.56% were male and 34.43% were female. Exploratory factor analysis was conducted for SF-36 based on the eight subscales, using the polychoric correlation and varimax rotation. Four items (MH26, MH30, SF20 and SF32) were loaded on different subscale which had low standardized estimates. KMO value was determined to be 0.816 and the barlett’s test for sphericity examination resulted in a statistically significance (p<0.001). Reliability test was performed for each domain and were found to be statistically significant. Conclusion: In conclusion, the research indicates that the utilization of SF36 in the Hindi language is deemed appropriate for estimation the quality of life in adults within Indian population.
Keywords: Health Related Quality of Life; SF-36; Health Survey; Hindi questionnaire; Translation; validation